Stress Level of Nursing Students in Completing Final Project - Maulina; Nura Zaiyati; Arfiza Ridwan (Fakultas Ilmu-ilmu Kesehatan Universitas Jenderal Soedirman, 2023)
Background. The stress response can be experienced by anyone when something unpleasant, uncomfortable, or disturbing to someone's peace occurs. This is often experienced by some final-year students, who are required to be able to complete their final project (thesis) as a graduation requirement. Conditions felt by students such as feelings of anxiety, worry, lack of enthusiasm, excessive fatigue, feeling left behind by friends who are already at a faster stage, and difficulties in completing the final assignment (thesis) can cause a stress response. Aim. This study aim to identify the stress level of nursing students in the preparation of the final project. Methods. A cross-sectional study was conducted using the Perceived Stress Scale (PSS-10) questionnaire. Data collection was carried out by filling out a questionnaire that consisted of 2 parts, namely demographic data and the stress level variable experienced by the respondent within the last month. The sample in this study was 131 students who were taking thesis courses. The sampling technique is total sampling. Results. The results showed that 23 students were completing their final assignment (thesis) with low stress (17.6%), 106 respondents with moderate stress (80.9%), and 2 respondents with heavy stress (1.5%). Conclusion. The majority of students who are completing their final project (thesis) experience moderate stress. This shows that they feel an inconvenience or a burden but must still complete their duties to achieve a bachelor's degree.